2019
DOI: 10.1093/mnras/stz1819
|View full text |Cite
|
Sign up to set email alerts
|

Planetary magnetic field control of ion escape from weakly magnetized planets

Abstract: ABSTRACT Intrinsic magnetic fields have long been thought to shield planets from atmospheric erosion via stellar winds; however, the influence of the plasma environment on atmospheric escape is complex. Here we study the influence of a weak intrinsic dipolar planetary magnetic field on the plasma environment and subsequent ion escape from a Mars-sized planet in a global three-dimensional hybrid simulation. We find that increasing the strength of a planet’s magnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 94 publications
(95 reference statements)
3
55
0
Order By: Relevance
“…In a recent hybrid study, Egan et al. (2019) investigated how the solar wind interacts with a Mars‐sized planet, its ionosphere and the resulting ion escape. This planet has been assigned a weak dipole field.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In a recent hybrid study, Egan et al. (2019) investigated how the solar wind interacts with a Mars‐sized planet, its ionosphere and the resulting ion escape. This planet has been assigned a weak dipole field.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…MHD simulations of present Mars with a weak dipole field also indicated that the existence of a weak intrinsic global dipole magnetic field increases ion loss . Some hybrid simulation studies reported the same effects of a weak intrinsic magnetic field on ion loss, while they also showed that the existence of a strong intrinsic magnetic field reduces ion loss (Egan et al, 2019;Kallio & Barabash, 2012). Investigating more precise contributions of an intrinsic magnetic field to ion loss is important for understanding the evolution of the atmosphere and the climate of Mars.…”
Section: Introductionmentioning
confidence: 96%
“…This is, for example, what is believed to have happened to Mars, which does not have an intrinsic magnetic field, therefore lacking a protective 'umbrella' against the solar wind. Recently, there has been a debate in the literature whether this is indeed the case, with some authors arguing that magnetic fields do not affect atmospheric escape, with Mars and Earth being counter examples of unmagnetised and magnetised planets, respectively, with similar outflow rates (Strangeway et al 2010, see also Blackman & Tarduno 2018;Egan et al 2019). Although escape in solar system planets can help us understand exoplanet evaporation (or atmospheric survival), the different, and often very extreme, architectures of exoplanetary systems compared to the solar system does not necessary guarantee that the same evaporation mechanisms taking place in the solar system would operate (or be as strong) in the exoplanets knows to date.…”
Section: Atmospheric Creation or Evaporationmentioning
confidence: 99%